Anti-Obesity Effect of Fermented Panax notoginseng Is Mediated Via Modulation of Appetite and Gut Microbial Population - Shin, Na Rae; Bose, Shambhunath; Choi, Yura; Kim, Young-Mi; Chin, Young-Won; Song, Eun-Ji; Nam, Young-Do; Kim, Hojun (Frontiers in Pharmacology, 2021)
Panax notoginseng (PN) is a traditional herbal medicine containing several active compounds such as saponins and ginsenosides with many therapeutic applications including anti-obesity activity. Fermentation by lactic acid bacteria has the potential to metabolize ginsenosides to more active forms. This study examined whether fermentation has any benefits on the protective effects of a PN extract against obesity using a high-fat diet (HFD)-fed mouse model. PN was fermented with Lactobacillus plantarum which exhibited high β-glucosidase activity. Upon fermentation, the PN extract exhibited an altered ginsenoside profile, a dramatic increase in the lactate level. Treatment of the HFD group with fermented PN (FPN), but not PN, decreased both the food and calorie intake significantly, which was consistent with the more potent suppressing effects of FPN than PN on the signaling pathways involved in appetite and energy intake. The PN treatment also modulated the gut microbial composition. The PN and FPN treatment groups showed clear differences in the population of gut microbiota. The relative abundance of Bacteroidetes, Erysipelotrichaceae, Coprococus, and Dehalobacterium were significantly higher in the FPN group then the normal, HFD, and XEN groups. Furthermore, the relative abundances of Akkermansia, Dehalobacterium, Erysipeliotrichaceae and parpabacteroides were significantly higher in the FPN group than the PN group, but the relative abundances of Allobaculum, Erysipelotrichi and Erysipelotrichale were significantly lower. The relative abundance of Bacteroides and Lactococcus was significantly higher and lower, respectively in the PN and FPN groups than the HFD group. In conclusion, the altered ginsenoside and organic acid’s profile, and altered gut microbial composition are believed to be the major factors contributing to the anti-obesity properties of FPN.